Analysis of the ipsilateral and the contralateral foot in patients admitted with diabetic foot complication through Amit Jain’s triple assessment for foot in diabetes - Jain, Amit Kumar C.; Jabbar, Saniya; S., Gopal (International Surgery Journal, 2018)
Background: Diabetic foot is a well-known complication of diabetes. The aim of this study was to determine the foot evaluation done in surgical patients admitted with diabetic foot problems and to distribute the components of evaluation through Amit Jain’s triple assessment for foot in diabetes. Methods: A descriptive retrospective analysis was carried out in Department of Surgery of Rajarajeswari Medical College, Bangalore, India. The study was approved by Institutional ethics committee. Results: 50 inpatients files of surgery patients were reviewed. Majority of patients were males. The most common diagnosis was non-healing ulcer affecting 34% of patients. Around 26% of patients had diagnosis written as just Diabetic Foot without mentioning the pathological lesion. 38% of patients didn’t have duration of diabetes mellitus mentioned in records. Although 94% of patients had ipsilateral foot examined, the component distribution like feeling the peripheral pulses and testing sensation for neuropathy was only 42% and 2%. The contralateral foot was examined in only 2% of patients. Conclusions: Diabetic foot is often neglected by patients and health care professionals. This study that analyzes diabetic foot evaluation through Amit Jain’s triple assessment for foot shows that although the ipsilateral foot is inspected in 94% of the patients, only 42% patient’s pulses were assessed and only 2% patients’ sensation were tested. The contralateral foot wasn’t examined in 98% of patients. Amit Jain’s triple assessment should be considered a minimum and mandatory evaluation tool for all patients with diabetic foot.